Comparative efficacy of hot and cold-water immersion therapies on post-match recovery in futsal players: a quasi-experimental study of muscle soreness, strength, and knee range of motion / Nur Syasya Mohammad Effendy ... [et al.]. - Mohammad Effendy, Nur Syasya; Mohamed, Muhamad Noor; Azreen, Noor Azila; Raja Hussein, Raja Nurul Jannat; Adnan, Muhamad Aizzat; Shaari, Maisharah; Mazaulan, Mardiana (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Hot and cold-water immersion therapies are popular recovery strategies for athletes [1]. This study investigates their effects on muscle soreness among futsal players, aiming to clarify their comparative benefits and mechanisms for optimizing post-exercise recovery [2]. This quasi-experimental study involves 18–25-year-old male futsal players from UiTM Negeri Sembilan, who are healthy and injury-free [3]. Baseline assessments include muscle soreness using the Visual Analog Scale (VAS) [4] and goniometer [5], sit-to-stand performance [6], knee extensor strength [7], and knee range of motion (ROM) [8]. After a 90-minute match, players undergo either hot (38–40°C) or cold-water immersion (11–15°C) for 15 minutes [9]. Muscle soreness and ROM are evaluated immediately post-intervention and at 24-, 48-, and 72-hours using repeated measures ANOVA.